Evaluating the cost-effectiveness of an early detection of Parkinson's disease through innovative technology. Issue 2 (3rd April 2017) - Muñoz, David A.; Kilinc, Mehmet Serdar; Nembhard, Harriet B.; Tucker, Conrad; Huang, Xuemei
ABSTRACT: Early detection of Parkinson's disease (PD) is critically important because it can increase patient quality of life and save treatment costs. An innovative approach for early detection of PD is to use nonwearable sensors that are capable of capturing skeletal joint data. This article evaluates the cost-effectiveness of this sensor-based intervention considering the quality-adjusted life years (QALYs) and the associated costs. The results indicate that the intervention would be cost-effective if devices were deployed for community health screening in public places such as health fairs and pharmacies.